2018
DOI: 10.1038/s41598-018-31721-x
|View full text |Cite
|
Sign up to set email alerts
|

Improved high temperature radiation damage tolerance in a three-phase ceramic with heterointerfaces

Abstract: Radiation damage tolerance for a variety of ceramics at high temperatures depends on the material’s resistance to nucleation and growth of extended defects. Such processes are prevalent in ceramics employed for space, nuclear fission/fusion and nuclear waste environments. This report shows that random heterointerfaces in materials with sub-micron grains can act as highly efficient sinks for point defects compared to grain boundaries in single-phase materials. The concentration of dislocation loops in a radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Two different SPS samples were prepared for this study, as reported previously [35] . Both SPS samples were sintered at 950°C for 5 min using heating rate of 100°C/min under 100 MPa.…”
Section: Spark Plasma Sinteringmentioning
confidence: 99%
“…Two different SPS samples were prepared for this study, as reported previously [35] . Both SPS samples were sintered at 950°C for 5 min using heating rate of 100°C/min under 100 MPa.…”
Section: Spark Plasma Sinteringmentioning
confidence: 99%
“…In this study, the successful capture, concentration and retention of radionuclides and formation of interfacial U-REE phases is associated with the crystallisation of spinel, periclase and olivine group minerals typical of a lower mantle (high P-T) assemblage. Both periclase and spinel are inherently tolerant to radiation-induced amorphization [40][41][42] and hence, the potential release of contained radionuclides. These two phases constitute ~ 95% of the recrystallised HTC mineralogy.…”
Section: Discussionmentioning
confidence: 99%
“…This has actually been thought to improve the radiation tolerance of multiphase materials. 94 For systems without or with low [MoO 3 ], the allowable relaxation time correlated with ΔT = T PS -T g is shorter meaning that phases B and C will be compositionally more similar than if a longer relaxation time was available for additional SiO 2 to move out of phase B. Therefore, it is theorized that accumulated damage was more uniform within these phases, thus enabling a thermal relaxation type coalescence of phase C particles similar to that occurring during cooling.…”
Section: Mechanism Of Radiation Damagementioning
confidence: 99%